SIR integrated model based on Runge-Kutta for Polio vaccination analysis - Caicai, Feng; Saratha Sathasivam,; Thing, Chee Hong; Kang, Yi Hao; Clement, Hii Kiing Yion (Penerbit Universiti Kebangsaan Malaysia, 2023)
Polio was one of the most lethal acute viral infectious diseases in the 20th century. A great deal of success has been achieved since the implementation of the polio vaccination strategy in 1988, and wild polio cases have decreased by more than 99%. However, in recent years, during the COVID-19 pandemic, vaccination strategies have encountered difficulties and challenges. At this stage, we are faced with the question of whether vaccination strategies should be continued. To determine the effect of vaccination strategies on the spread of polio at this stage, this paper proposes to use the SIR model based on world data collected in 2021 to simulate the 30-days transmission process of polio with and without vaccination. In addition, the results of this model also provide us with a reference disease response plan. The simulation results show that the vaccinated polio transmission model performs better than the uninoculated polio transmission model in terms of average estimated infection case, reproduction number, and infection rate, etc. At this stage, polio will not become an endemic disease if it occurs in vaccination areas. Nevertheless, if the case occurs in an unvaccinated area, the disease may develop into an endemic disease, and we must take immediate action (increase social distance, isolation, etc.) to effectively control its spread.